Cesarean section at maternal request - Guevara Ríos, Enrique (2023)
Cesarean section is a life-saving intervention with medical indications. Cesareansection is clinically indicated when there is a significant risk of adverse consequencesfor the pregnant woman or the fetus. However, in recent years non-medical indicationsfor cesarean section such as cesarean section by maternal request have emerged.This is a non-systematic review of cesarean section at maternal request. Cesareandelivery at mother's request compared to planned vaginal delivery is a multifacetedand complex issue, the data are minimal and mostly based on indirect comparisons,and its implications for women of childbearing age. health professionals and societyare unknown. For physicians, performing cesarean section for non-medical reasonsis a professional decision, the ethics of which is being debated without sufficientevidence on the risks and benefits.